Excipient-Free Pure Drug Nanoparticles Fabricated by Microfluidic Hydrodynamic Focusing - Roni Sverdlov Arzi; Asaf Kay; Yulia Raychman; Alejandro Sosnik (MDPI AG, 2021)
Nanoprecipitation is one of the most versatile methods to produce pure drug nanoparticles (PDNPs) owing to the ability to optimize the properties of the product. Nevertheless, nanoprecipitation may result in broad particle size distribution, low physical stability, and batch-to-batch variability. Microfluidics has emerged as a powerful tool to produce PDNPs in a simple, reproducible, and cost-effective manner with excellent control over the nanoparticle size. In this work, we designed and fabricated T- and Y-shaped Si-made microfluidic devices and used them to produce PDNPs of three kinase inhibitors of different lipophilicity and water-solubility, namely imatinib, dasatinib and tofacitinib, without the use of colloidal stabilizers. PDNPs display hydrodynamic diameter in the 90-350 nm range as measured by dynamic light scattering and a rounded shape as visualized by high-resolution scanning electron microscopy. Powder X-ray diffraction and differential scanning calorimetry confirmed that this method results in highly amorphous nanoparticles. In addition, we show that the flow rate of solvent, the anti-solvent, and the channel geometry of the device play a key role governing the nanoparticle size.